2018
DOI: 10.3892/etm.2018.5683
|View full text |Cite
|
Sign up to set email alerts
|

The medium and long-term effect of electrophysiologic monitoring on the facial nerve function in minimally invasive surgery treating acoustic neuroma

Abstract: The medium and long-term effects of electrophysiologic monitoring on the facial nerve function in minimally invasive surgery treating acoustic neuroma were studied. Sixty-two patients with acoustic neuroma taking minimally invasive surgeries in Dezhou Hospital from August 2014 to September 2015 were selected and randomly divided into 29 cases of the control group and 33 cases of the observation group. Intraoperative electrophysiologic monitoring was applied to the observation group, but not to the control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
3
0
1
Order By: Relevance
“…This study showed that the proximal stimulation threshold, proximal-to-distal amplitude ratio, and proximal amplitude could, to some extent, predict facial nerve functioning within seven days after acoustic neuroma resection. All three indicators were similar to those reported previously (11,13). This study's sensitivity and specificity results indicated that the proximal-to-distal amplitude ratio was the best predictor of facial nerve functioning.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study showed that the proximal stimulation threshold, proximal-to-distal amplitude ratio, and proximal amplitude could, to some extent, predict facial nerve functioning within seven days after acoustic neuroma resection. All three indicators were similar to those reported previously (11,13). This study's sensitivity and specificity results indicated that the proximal-to-distal amplitude ratio was the best predictor of facial nerve functioning.…”
Section: Discussionsupporting
confidence: 88%
“…Several electrophysiological technology reports have predicted the facial nerve's postoperative functioning (11). However, few have detailed the procedures used to locate the nerve accurately.…”
Section: Introductionmentioning
confidence: 99%
“…Moderate adhesions may damage the nerve, and severe adhesions may lead to separation of nerve fibers [ 16 ]. Although Hou [ 18 ] believed that small acoustic neuromas rarely infiltrate the facial nerve, this conclusion could not be applied to all patients. At present, it is believed that the adhesion degree of small tumor and facial nerve can also directly affect the surgical effect [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, it was important to identify the left RLN and to perform esophagectomy without nerve damage, and we decided to use intraoperative RLN monitoring. Intraoperative nerve monitoring is commonly performed in the field of otolaryngologic and head and neck surgery, and numerous reports of its beneficial effect in preventing RLN palsy have been published [12,13]. In this case, it was particularly difficult to grasp the anatomy around the DA, but the position of the left RLN could be easily confirmed by the magnified views offered by the thoracoscopic approach and RLN monitoring, and esophagectomy was successfully performed without nerve damage.…”
Section: Discussionmentioning
confidence: 88%